A potent and selective C-11 labeled PET tracer for imaging sphingosine-1-phosphate receptor 2 in the CNS demonstrates sexually dimorphic expression1. Issue 29 (7th August 2015) - Yue, Xuyi; Jin, Hongjun; Liu, Hui; Rosenberg, Adam J.; Klein, Robyn S.; Tu, Zhude
<x xml:space="preserve">Abstract</x> Sphingosine-1-phosphate receptor 2 (S1PR2) plays an essential role in regulating blood–brain barrier (BBB) function during demyelinating central nervous system (CNS) disease.